Pengaruh Media Sosial terhadap Partisipasi Kewargaan Pemuda: Studi Empiris di Kabupaten Sleman, Daerah Istimewa Yogyakarta - Saputra, Rizky Aditya; Nugroho Prasetyo, Fajar (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2024)
This study examines the influence of social media on youth civic participation in Sleman Regency, Special Region of Yogyakarta. The study is grounded in the growing intensity of social media use among young people and its potential role in shaping civic engagement at the local level. A quantitative approach with an explanatory research design was employed. Data were collected through a survey of 300 youths aged 17 to 30 years, selected using stratified random sampling. A structured questionnaire was used to measure social media use and levels of civic participation. Data analysis included descriptive statistics, Pearson correlation, and multiple linear regression. The findings reveal that social media use has a positive and significant effect on youth civic participation. The effect is stronger on social participation than on formal political participation. Social media use for information seeking and public issue discussion contributes more significantly than entertainment-oriented use. The study concludes that social media functions as an effective supporting tool for enhancing youth civic participation when used in a substantive and context-aware manner. These findings provide empirical evidence to inform local youth policies and digital-based civic engagement programs.